Serial Recombineering Cloning to Build Selectable and Tagged Genomic P[acman] BAC Clones for Selection Transgenesis and Functional Gene Analysis using Drosophila melanogaster. Issue 2 (9th February 2023) - Venken, Koen J. T.; Matinyan, Nick; Gonzalez, Yezabel; Dierick, Herman A.
Abstract: Transgenes with genomic DNA fragments that encompass genes of interest are the gold standard for complementing null alleles in rescue experiments in the fruit fly Drosophila melanogaster . Of particular interest are genomic DNA clones available as bacterial artificial chromosomes (BACs) or fosmids from publicly available genomic DNA libraries. Genes contained within BAC and fosmid clones can be easily modified by recombineering cloning to insert peptide or protein tags to localize, visualize, or manipulate gene products, and to create point mutations or deletions for structure‐function analysis of the inserted genes. However, since transgenesis efficiency is inversely correlated with transgene size, obtaining transgenic animals for increasingly larger BAC and fosmid clones requires increasingly laborious screening efforts using the transgenesis marker commonly used for these transgenes, the dominant eye color marker white + . We recently described a drug‐based selectable genetic platform for Drosophila melanogaster, which included four resistance markers that allow direct selection of transgenic animals, eliminating the need to identify transgenic progeny by laborious phenotypic screening. By integrating these resistance markers into BAC transgenes, we were able to isolate animals containing large transgenes by direct selection, avoiding laborious screening. Here we present procedures on how to upgrade BAC clones by serial recombineering cloning to build both selectable and tagged BAC transgenes, for selection transgenesis and functional gene analysis, respectively. We illustrate these procedures using a BAC clone encompassing the gene encoding the synaptic vesicle protein, cysteine string protein. We demonstrate that the modified BAC clone, serially recombineered with a selectable marker for selection transgenesis and an N‐terminal green fluorescent protein tag for gene expression analysis, is functional by showing the expression pattern obtained after successful selection transgenesis. The protocols cover: (1) cloning and preparation of the recombineering templates needed for serial recombineering cloning to incorporate selectable markers and protein tags; (2) preparing electrocompetent cells needed to perform serial recombineering cloning; and (3) the serial recombineering workflow to generate both selectable and tagged genomic BAC reporter transgenes for selection transgenesis and functional gene analysis in Drosophila melanogaster . The protocols we describe can be easily adapted to incorporate any of four selectable markers, protein tags, or any other modification for structure‐function analysis of the genes present within any of the BAC or fosmid clones. A protocol for generating transgenic animals using serially recombineered BAC clones is presented in an accompanying Current Protocols article (Venken, Matinyan, Gonzalez, & Dierick, 2023a). © 2023 Wiley Periodicals LLC. Basic Protocol 1 : Cloning and preparation of recombineering templates used for serial recombineering cloning. Basic Protocol 2 : Making electrocompetent cells of the bacterial strains used to perform serial recombineering cloning or induction of plasmid copy number. Basic Protocol 3 : Serial recombineering cloning to generate both selectable and tagged genomic P[acman] BAC reporter transgenes for selection transgenesis and gene expression analysis in Drosophila melanogaster .